From party politics to militarism in Japan, 1924-1941 - Kitaoka, Shin'ichi 1948- (2021)
"Captures the essence of the complex pre-World War II period in Japan's political history"
"First published in Japanese as Nihon no kindai 5: Seita?o kara gunbu e 1924-1941, A?2013"--Title page verso.
Includes bibliographical references (pages 347-356) and index.
Keywords: Political parties -- Japan -- History -- 20th century; Militarism -- Japan -- History -- 20th century; Japan -- Politics and government -- 1926-1945.; Japan -- Armed Forces -- Political activity -- History -- 20th century